2019
DOI: 10.1002/maco.201910962
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Tafel coefficients according to passive/active state of steel carbonation‐induced corrosion in concrete

Abstract: Statistical quantification of Tafel coefficients is investigated in this study for isolated steel rebar embedded in concrete. The survey is supported by a wide experimental campaign carried out earlier to characterize the passive and active states of carbonation‐induced corrosion of steel. Electrochemical measurements (polarization resistance, corrosion potential, Tafel coefficients) and gravimetric estimations of iron loss were regularly conducted over 417 days on 108 concrete specimens. The statistical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…However, Duprat et al [ 19 ] reported a mean value of βnormala,normala of 868 mV/dec in carbonated samples, these values are very high considering the active corrosion state of steel rebars. The geometry of the samples in the case of Duprat et al [ 19 ] was very different than what is employed in this study. They reported the parameters on steel rebar embedded in block samples, such geometry does not allow for uniform polarization of the whole steel surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Duprat et al [ 19 ] reported a mean value of βnormala,normala of 868 mV/dec in carbonated samples, these values are very high considering the active corrosion state of steel rebars. The geometry of the samples in the case of Duprat et al [ 19 ] was very different than what is employed in this study. They reported the parameters on steel rebar embedded in block samples, such geometry does not allow for uniform polarization of the whole steel surface.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, electrochemical corrosion parameters are expected to be dissimilar. Duprat et al [ 19 ] reported the corrosion parameters in carbonated and noncarbonated concrete. The mean values of βa and βc, were 868 and 473 mV/dec for active steel in carbonated concrete, respectively, whereas, for the passive steel, the values were 637 and 218 mV/dec, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…β ), and the rebar potential E [48,49]. The oxygen concentration was not implemented in the Butler-Volmer equation as its reduction is suspected to be the rate-determining step only when all dissolved and gaseous O 2 is depleted within concrete, which occurs only after a long period under permanent saturation [50,51].…”
Section: Figurementioning
confidence: 99%
“…Without knowing the charge-transfer coefficients, an error will be introduced during calculation of the corrosion rate. However, according to experimental values of β a and β c in the literature [5,48,49,88,89], this error should be a factor of 10 at most when the charge-transfer coefficients are unknown.…”
Section: Towards a Quantification Of The Corrosion Rate In Non-uniform Corrosion?mentioning
confidence: 99%
“…Monzon et al [ 32 ] studied the corrosion rate of reinforced concrete by linear polarization method and electrochemical impedance spectroscopy (EIS) and analyzed various electrochemical parameters by partial least squares. Duprat et al [ 33 ] studied the statistical quantification of the Tafel coefficient of steel bars in concrete. Chang et al [ 34 ] evaluated the corrosion rate and Tafel parameters of three types of steel bars in concrete, new steel bars, and corroded steel bars in seawater.…”
Section: Introductionmentioning
confidence: 99%